2013
DOI: 10.1007/s10661-013-3421-y
|View full text |Cite
|
Sign up to set email alerts
|

Human factors and tidal influences on water quality of an urban river in Can Tho, a major city of the Mekong Delta, Vietnam

Abstract: In this study, we focused on water quality in an urban canal and the Mekong River in the city of Can Tho, a central municipality of the Mekong Delta region, southern Vietnam. Water temperature, pH, electrical conductivity, BOD5, CODCr, Na(+), Cl(-), NH4 (+)-N, SO4 (2-)-S, NO3 (-)-N, and NO2 (-)-N for both canal and river, and tide level of the urban canal, were monitored once per month from May 2010 to April 2012. The urban canal is subject to severe anthropogenic contamination, owing to poor sewage treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…Fish were held in aerated 3000 l tanks fitted with a recirculating biofiltration system and kept on a 12 h:12 h light:dark photoperiod. Water Cl − and pH in these holding conditions were 0.35 mmol l −1 and 7.2±0.1, respectively, which is similar to that listed for native habitat in the nearby Mekong River (in mmol l −1 : Ozaki et al, 2014;Kongmeng and Larsen, 2014). Fish were fed to satiation once daily with commercial dry pellets obtained from a local supplier and held under these conditions for at least 3 weeks prior to experimentation.…”
Section: Materials and Methods Animal Husbandrysupporting
confidence: 75%
“…Fish were held in aerated 3000 l tanks fitted with a recirculating biofiltration system and kept on a 12 h:12 h light:dark photoperiod. Water Cl − and pH in these holding conditions were 0.35 mmol l −1 and 7.2±0.1, respectively, which is similar to that listed for native habitat in the nearby Mekong River (in mmol l −1 : Ozaki et al, 2014;Kongmeng and Larsen, 2014). Fish were fed to satiation once daily with commercial dry pellets obtained from a local supplier and held under these conditions for at least 3 weeks prior to experimentation.…”
Section: Materials and Methods Animal Husbandrysupporting
confidence: 75%
“…Our study revealed that the nutrient concentration was highest mainly along the delta canals, especially the concentration of TP which ranged from 0.13 mgL -1 in cluster 1b2 to 0.56 mgL -1 in cluster 2. Previous studied have concluded that the pollution from Can Tho city could affect human health within the delta [ 12 , 47 ]. Besides, pH and DO were depleted for most of the sites due to the decomposition of organic matter and storm runoff affected by land use in acid sulfate soils [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Mekong delta, many studies have shown surface water pollution in the man-made canals and some densely populated cities such as Chau Doc, Can Tho, My Thaun, that could threaten human, animal and ecosystem health given the fact that this water source is intensively used for drinking, irrigation and domestic services [ 12 14 ]. In Thailand, water quality monitoring by the Pollution Control Department (PCD) revealed that 68% of water bodies were suitable for use by agriculture and for general consumption being of good and moderate quality but no surface water was categorized as being of very good quality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, floods due to seasonal high river discharges upstream, high tides and high rainfall intensity are a significant issue that Can Tho is facing [ 15 , 16 ]. In addition, water pollution from untreated wastewater and illegal garbage discharge is another problem of this city [ 17 ]. During flooding time, polluted water causes some health-related issues to local people, for example diarrhea.…”
Section: Introductionmentioning
confidence: 99%